Investigating the Role of self-Learning in Acquiring English as Foreign language at Sudanese Tertiary Level - Dr. Haroun Khatir Abdalla Shashd; Amar Abd El Rsoul Bushra Adam; Amna Eltayeb Ali Gassmalla (White Nile Journal for Studies and Research, 2021)
This study aims at investigating the role of using self learning strategies in the performance of Sudanese EFL students. The descriptive analytical method was applied to conduct the study. The tool used for data collection was questionnaire for Sudanese EFL university students. The sample of the study was from El imam Elmahdi University, Ahfad University of Women and University of Medical Science and Technology. It consists of 120 students, 60 male and 60 female The samples that chosen to conduct this study are 2nd years university students.. The EFL instructors were chosen randomly from different universities. Data was analyzed by using (SPSS) program to analyze the students' questionnaire. the findings of the research are as follow: The students implements a lot of strategies that help them to learn English language, and The curricula are not prepared well to achieve learning autonomy, the students have strong desire to adopt self-learning in learning English. In the light of the finding, the researcher put forward the following recommendations New strategies of teaching students to adopt self learning should be adopted by the universities in the Sudan. Teachers of English language at Sudanese universities should be trained to teach English to help students to adopt factors help them in self learning. EFL curriculum designers should consider the issues of self-learning.